Chemical and structural composition of black pigmented supragingival biofilm of bovines with periodontitis - Saraiva, Júlia Rebecca [UNESP]; Ramos, Marcelle Marie B.; Borsanelli, Ana Carolina [UNESP]; Schweitzer, Christiane M. [UNESP]; Júnior, Elerson Gaetti-Jardim [UNESP]; Höfling, José Francisco; Ramos, Thamiris Naiasha M. [UNESP]; Dutra, Iveraldo S. [UNESP] (FapUNIFESP (SciELO), 2019)
Bovine periodontitis is a multifactorial disease primarily associated with a potentially pathogenic microbiota housed in the oral biofilm of animals. Biofilms are organized structures, in which the constituents coexist in symbiosis, already described as a predisposing factor to periodontitis in other species. The objective of the present study was to characterize the structure and chemical aspects of the bovine black pigmented supragingival biofilm using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS), respectively, and determine its relationship with bovine periodontitis. Eleven premolar teeth from different animals were evaluated; five non-pigmented samples and six samples with black pigmented biofilms were initially submitted to SEM, and three areas of these samples were selected for EDS. The structure of the pigmented biofilm was more complex and irregular because of a higher content of mineral elements. The semi-quantitative EDS data indicated an association of iron (p<0.014) and magnesium (p<0.001) with the occurrence of periodontitis, whereas carbon, phosphorus, calcium, manganese, sodium, and potassium were not associated with the disease. Carbon (p<0.039), manganese (p<0.007), and iron (p<0.015) were associated with pigmentation, whereas phosphorus, calcium, and magnesium were not associated with it. Spearman correlation test showed the relationships between calcium and phosphorus, and iron and silicon. The strong association of iron in the pigmented supragingival biofilm and with the occurrence of periodontitis suggests the presence of microorganisms that use this element in their metabolism and that are also associated with bovine periodontitis. This study suggests that the pigmented deposits in the crown of the teeth of cattle are an true biofilm with the deposition of iron, and it indicates that the presence of iron and magnesium in these formations may be involved in the metabolism of some microorganisms associated with the etiology of bovine periodontitis.
Composição química e estrutural do biofilme supragengival pigmentado de bovinos com periodontite
Keywords: Bovine; Energy dispersive spectroscopy; Periodontitis; Scanning electron microscopy; Supragingival biofilm